f(x) = 4x^2 – 17x + 3
The equation is written in the form:
f(x) = ax^2 + bx + c
Where:
a= 4
b= -17
c= 3
Apply the quadratic formula:
![\frac{-b\pm\sqrt[]{b^2-4\cdot a\cdot c}}{2\cdot a}](https://img.qammunity.org/2023/formulas/mathematics/college/6ll9xrpkhophltqj6goc56svs0vp43p5j4.png)
Replace:
![\frac{-(-17)\pm\sqrt[]{(-17)^2-4\cdot4\cdot3}}{2\cdot4}](https://img.qammunity.org/2023/formulas/mathematics/college/eqyy16wvbqy4ypm4j1bvp6540tvf880d8r.png)
The discriminant is the part of the quadratic formula under the square root:
b^2-4*a*c = (-17)^2- (4 * 4 *3 ) = 289- 48 =241
Discriminant = 241
Since the discriminant is greater than zero, the equation has 2 distinct real roots.